A dual functional peptide carrying in vitro selected catalytic and binding activities1. Issue 38 (14th October 2015) - Zhu, Liping; Wang, Wei; Zhao, Haixu; Xu, Muye; Tada, Seiichi; Uzawa, Takanori; Liu, Mingzhe; Ito, Yoshihiro
<x xml:space="preserve">Abstract</x> When minimal functional sequences are used, it is possible to integrate multiple functions on a single peptide chain, like a "single stroke drawing".